2018
DOI: 10.1073/pnas.1717978115
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and structural architecture of polyQ aggregates in yeast

Abstract: Huntington's disease is caused by the expansion of a polyglutamine (polyQ) tract in the N-terminal exon of huntingtin (HttEx1), but the cellular mechanisms leading to neurodegeneration remain poorly understood. Here we present in situ structural studies by cryo-electron tomography of an established yeast model system of polyQ toxicity. We find that expression of polyQ-expanded HttEx1 results in the formation of unstructured inclusion bodies and in some cases fibrillar aggregates. This contrasts with recent fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
74
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 54 publications
(74 reference statements)
7
74
2
Order By: Relevance
“…In some cases, ER tubes surrounded the aggregate periphery and tunnelled through its interior ( Supplementary Fig. S4f), similar to previous observations for polyQ and heat-shock induced aggregates (Bauerlein et al, 2017;Gruber et al, 2018;Wagner et al, 2017). However, in contrast to polyQ fibrils in neurons (Bauerlein et al, 2017), β protein fibrils did not appear to deform cellular membranes ( Supplementary Fig.…”
Section: Ultrastructure Of Neuronal β Protein Aggregatessupporting
confidence: 88%
See 1 more Smart Citation
“…In some cases, ER tubes surrounded the aggregate periphery and tunnelled through its interior ( Supplementary Fig. S4f), similar to previous observations for polyQ and heat-shock induced aggregates (Bauerlein et al, 2017;Gruber et al, 2018;Wagner et al, 2017). However, in contrast to polyQ fibrils in neurons (Bauerlein et al, 2017), β protein fibrils did not appear to deform cellular membranes ( Supplementary Fig.…”
Section: Ultrastructure Of Neuronal β Protein Aggregatessupporting
confidence: 88%
“…The ER around the aggregates often engaged in membrane contact sites with mitochondria ( Supplementary Fig. S3b, d), as observed for stress-induced and polyQ aggregates (Gruber et al, 2018;Zhou et al, 2014). Altogether, the morphology and cellular interactions of β protein aggregates were reminiscent of those formed by natural aggregating proteins.…”
Section: Ultrastructure Of Neuronal β Protein Aggregatesmentioning
confidence: 63%
“…In HD, aggregation of mHTT derives from an elongated poly(Q)-stretch in exon-1 ( Taylor et al, 2002 ), which can also be observed in yeast models of HD ( Krobitsch and Lindquist, 2000 ; Meriin et al, 2002 ; Ocampo and Barrientos, 2011 ; Kaiser et al, 2013 ). Recently, the ultrastructural architecture of a GFP-tagged human exon1-97Q construct was explored in yeast ( Gruber et al, 2018 ). Both fibrillar and – to a major part – unstructured inclusions were found, while no detrimental interactions with cellular membranes were seen ( Gruber et al, 2018 ).…”
Section: Cytotoxic Mechanisms In Hd Yeast Modelsmentioning
confidence: 99%
“…Recently, the ultrastructural architecture of a GFP-tagged human exon1-97Q construct was explored in yeast ( Gruber et al, 2018 ). Both fibrillar and – to a major part – unstructured inclusions were found, while no detrimental interactions with cellular membranes were seen ( Gruber et al, 2018 ). This stands at odds with previous findings of a similar construct forming amyloid-like fibrils in mammalian cells that interact with endomembranes, preferentially those of the ER ( Bäuerlein et al, 2017 ).…”
Section: Cytotoxic Mechanisms In Hd Yeast Modelsmentioning
confidence: 99%
See 1 more Smart Citation